PENINGKATAN KETERAMPILAN MEMBACA BAHASA ARAB MELALUI TEKNIK LOOK AND SAY (Penelitian Tindakan Siswa Kelas IV SDIT Segar Amanah) - Reza Indrawan; Emzir Emzir; Endry Boeriswati (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTRACT This research aims to improve the Arabic reading skills of fourth grade of SDIT Segar Amanah students through the Look and Say technique. The subjects of this research were 32 students of fourth grade SDIT Segar Amanah. This research used a Classroom Action Research method with a model from Kemmis and Mc Taggart which consisted of planning, acting and observing, and reflecting throughout 2 cycles. The data was collected using test and observation guidelines for teaching and learning activities and observation guidelines for teacher and student. This research shows that the Look .and Say technique can improve students' reading skills in Arabic with the difference in the results of the pre-test, post-test cycle 1 and post-test cycle 2 with the class average score in the pre-test is 49.5. Then the average score results in the post test cycle 1 was 67.2 and the result of the class average score in the post-test 2 was 78.3. Keywords : Arabic Reading Skills, Look and Say